Evaluation of the maternal and fetal risk factors associated with neonatal care unit hospitalization time. (1st November 2016) - Kurek Eken, Meryem; Tüten, Abdulhamit; Ozkaya, Enis; Dinçer, Emre; Şenol, Taylan; Karatekin, Güner; Karateke, Ateş
Abstract: Objective : To evaluate maternal and neonatal risk factors associated with the length of hospital stay in the neonatal intensive care unit (NICU). Material and method : This retrospective observational study was based on 3607 newborns who were admitted to the NICU of a tertiary teaching hospital from January 2012 through December 2014. Known obstetric risk factors associated with duration of hospitalization in NICUs were assessed including intrauterine growth restriction, maternal diabetes, oligohydramnios, chorioamnionitis, premeture rupture of membranes, preeclampsia, congenital malformations, neonatal sepsis, premature retinopathy, intracranial bleeding, necrotizing enterocolitis, meconium aspiration, maternal hypertension, fetal congenital cardiac malformations, congenital metabolic diseases, congenital hypothyroidism, pneumonia, pulmonary hypertension, bronchopulmonary dysplasia, pneumothorax and respiratory distress syndrome. Results : Gestational age (beta coefficient: −0.244, p <0.001) and birth weight (beta coefficient: −0.237, p <0.001) were significant confounders for duration of hospitalization in newborns. Conclusion : Gestational age and the birth weight were the most important confounders for duration of hospitalization. Neonate care in developing countries would further benefit from additional large population-based long-term studies with broad parameters.